2011
DOI: 10.1021/ja207407n
|View full text |Cite
|
Sign up to set email alerts
|

Structure of (5′S)-8,5′-Cyclo-2′-deoxyguanosine in DNA

Abstract: Diastereomeric 8,5′-cyclopurine 2′-deoxynucleosides, containing a covalent bond between the deoxyribose and the purine base, represent an important class of DNA damage induced by ionizing radiation. The 8,5′-cyclo-2′-deoxyguanosine lesion (cdG) has been recently reported to be a strong block of replication and highly mutagenic in Escherichia coli. The 8,5′-cyclopurine-2′-deoxyriboses are suspected to play a role in the etiology of neurodegeneration in xeroderma pigmentosum patients. These lesions cannot be rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(89 citation statements)
references
References 83 publications
7
82
0
Order By: Relevance
“…Experimentally, it has been found that the C5′• of dAdo or dGuo forms a bond with the C8 atom with a cyclization rate constant of 1.6 × 10 5 s −1 (Boussicault et al, 2008; Huang et al, 2011; Romieu et al, 1999). The C5′-C8 cycloguanine structure exists in two diastereoisomeric forms: (i) 5′(S),8-cyclo-2′-deoxyguanosin-7-yl and (ii) 5′ (R),8-cyclo-2′-deoxyguanosin-7-yl.…”
Section: Electron Reaction With Dnamentioning
confidence: 99%
“…Experimentally, it has been found that the C5′• of dAdo or dGuo forms a bond with the C8 atom with a cyclization rate constant of 1.6 × 10 5 s −1 (Boussicault et al, 2008; Huang et al, 2011; Romieu et al, 1999). The C5′-C8 cycloguanine structure exists in two diastereoisomeric forms: (i) 5′(S),8-cyclo-2′-deoxyguanosin-7-yl and (ii) 5′ (R),8-cyclo-2′-deoxyguanosin-7-yl.…”
Section: Electron Reaction With Dnamentioning
confidence: 99%
“…TG is a helix-distorting lesion that causes the damaged base to assume an extrahelical position [35]; therefore, it poses a formidable block to DNA synthesis past the lesion [36]. The cPu lesion is caused by a second covalent bond between the base and corresponding sugar, which perturbs normal helix twist and base stacking [37, 38]. The cPu adduct interferes with replication [39] and transcription [40].…”
Section: Single Oxidative Base Lesions Differentially Affect Unwindinmentioning
confidence: 99%
“…34 The S -cdG participates in Watson–Crick hydrogen bonding with the complementary dC. However, the S -cdG deoxyribose shifts to the O4′- exo pseudorotation with P = 280°.…”
Section: Introductionmentioning
confidence: 99%